What is the role of social pensions in Asia? - Armando Barrientos (Asian Development Bank Institute (ADBI), 2012)
Rapid population ageing and economic transformation in Asia raise the policy challenge of ensuring income security in old age. There is growing interest among policymakers in the potential role of noncontributory transfers as an instrument to address a variety of policy challenges, including old age poverty and vulnerability, rapid population ageing, the effects of migration on intergenerational family support structures, and the effects of informality on social protection systems. The main objective of this paper is to explore the potential role of social pensions and other noncontributory schemes in Asia, informed by insights from theory and international experience. The paper identifies alternative forms of providing income security in old age, including social pensions. It also examines the welfare effects of adopting alternative social pension designs, especially around two key policy nodes: the comparative advantages of social assistance and social pensions, and the integration of noncontributory transfers within advanced contributory pension schemes.
Keywords: H55; I38; J14; J32; O17; 330; social pensions; population ageing; asia; social assistance; noncontributory transfers; contributory pension schemes; Alternde Bevölkerung; Altersvorsorge; Grundbedürfnisse; Rentenreform; Wohlfahrtsanalyse; Asien